Kepuasan Masyarakat Dalam Playanan Pembuatan E-Ktp Di Kantor Camat Praya - Abdul Hamid; Mardi Mardi (Universitas Katolik Widya Karya Malang, 2023)
Public services that provide a service to clients is one of the important variables that provide an important commitment to create a good reputation and trust locally. Public protests in the form of long queues, helpless assistance, and actually bad offices do not satisfactorily influence the picture and quality of administrative levels in public areas. the research that I use is descriptive research. This research is called descriptive research with data collection techniques in this study using questionnaires. The population in this study are all people who are customers at the Praya District Office. The sampling technique used is nonprobability sampling technique. Based on the results of research conducted on 60 respondents regarding community perceptions and satisfaction with the services of the Praya District Office, it is measured based on community satisfaction using the Community Satisfaction Index (IKM) in terms of administrative services, the results obtained are Community Satisfaction Index per indicator where there are 14 indicators, namely ( 1) service procedures with a total IKM score of 76.66 included in the good category, (2) service requirements with a total IKM score of 68.33 included in the good category, (3) clarity of service officers with a total IKM score of 63.33 included in the good category, (4) the discipline of service officers with a total IKM score of 63.75 is included in the good category, (5) the responsibility of service officers with a total IKM value of 65.41 is included in the good category, (6) the ability of service officers with the total IKM score of 66.66 is included in the good category, (7) the speed of service with a total IKM score of 61.66 is included in the poor category, (8) the fairness of getting services with a total IKM score of 64.58 is included in the good category, (9) politeness and friendliness of staff with a total IKM score of 63.75 included in the good category, (10) fairness of service fees with a total IKM score of 65.83 included in the good category, (11) certainty of service fees with a total IKM score of 64.16 is included in the good category, (12) the certainty of service schedules with a total IKM value of 56.66 is included in the good category, (13) environmental comfort with a total IKM value of 66.66 is included in the good category and (14) environmental safety with a total IKM value of 66.25 included in the good category.